The handbook of public sector communication - Canel, María José; 1977- Luoma-aho, Vilma (Handbooks on communication and media, 2020)
Public sector organizations exist to make society function effectively. These organizations govern, serve citizens, and run the public sector and its services according to principles set by the government. In their communication, public sector organizations must balance the democratic communication aims of engaging citizens with organizational and institutional goals, as well as with survival in the midst of budget restrictions. The ultimate goal of public sector communication is to enable citizen welfare, but how this can be achieved in practice is both academically and professionally debated. In fact, public sector organizations' communication reflects the cultural and historical heritage of the society around them, and as such there is no one universal model of "good public sector communication." Models and practices that are effective in one societal setting may actually be detrimental in another. Despite this diversity, there appear to be similar challenges emerging for public sector organizations globally, and there is thus a need for a deeper understanding of how communication might be used to address these challenges. The aim of this handbook is to provide a comprehensive look at public sector communication. It describes and analyzes the contexts, policies, aims, issues, questions, and practices that shape public sector communication in order to understand the complex communication environment as well as the changing citizen and stakeholder expectations that public sector organizations are facing today. These chapters provide a comprehensive overview of current public sector communication research"--